Maximal lower extremity power output changes during a decathlon - Edouard, P.; Morin, J.-B.; Samozino, P. (New Studies in Athletics, 2013)
ABSTRACT This study sought to determine the changes in maximal leg power output over the course of a decathlon in order to better understand 1) the event's functional demands, 2) the muscular mechanical capabilities determining performance in the event, and 3) their relationships with injury risk factors. It was conducted under field conditions during the 2010 French National Combined Events Championships with six national-level athletes and 11 control participants as subjects. No differences in the values for squat jump and cycling sprint were found between tests at the beginning and end of each day (P>0.05), while significantly lower squat jump values at the start of the second day were reported for the control participants (P<0.05). The results suggest that a decathlon does not induce measurable alterations in lower extremity force, velocity or power output affecting performance and that the accumulation of fatigue (and/or neuromuscular fatigue, if any) does not play a major role in the injury risk associated with the event. The authors suggest that adapted wake-up and warmup routines are necessary before morning events, particularly the 110m hurdles on the second day, and that other injury risk factors should be explored.